Application of capillary electrophoretic methods for the analysis of plant phloem and xylem saps composition: A review - Melicherová, Natália; Řemínek, Roman; Foret, František (Journal of separation science, 2020)
Plant vascular tissue is essential for the exchange of water, nutrients, metabolic products, and signals among distant organs in cormophytes. The compositions of phloem and xylem saps are highly dependent on many internal and external factors, and thus their analysis provides a valuable insight into plant physiology, growth, and development as well as nutrition status or presence of biotic or abiotic stresses. Capillary electrophoresis characterized by highly efficient separations and minuscule sample requirements represents a suitable analytical technique for this purpose because the sap constitutes a complex mixture with generally minimal availability. This review aims at providing a comprehensive overview of published capillary electrophoretic methods for the analysis of primary components present in the phloem and xylem saps of higher plants.
Keywords: xylém; elektroforéza kapilární; Plants; phloem; plant metabolomics; floém; Xylem; xylem; Phloem; capillary electrophoresis; rostliny; sap; Electrophoresis, Capillary